Racial Disparities in Survival of Breast Cancer Patients After Surgery - Wang, Shuhan; Tang, Weifang; Wang, Shengying; Hong, Shikai; Liu, Jianjun (Frontiers in Public Health, 2022)
Introduction: The racial disparities of opportunity to receive the appropriate intervention and lower insurance coverage may result in survival disparities in different races. This study aims to provide a perspective on racial disparities in the survival of breast cancer patients after surgery. Methods: Through data from the Surveillance, Epidemiology, and End Results (SEER) program, this study estimated the survival of breast cancer patients of different races from 1998 to 2017. Inverse probability weighting (IPW) was utilized to adjust the imbalanced clinicopathological features of patients of different races. Results: This study analyzed 214,965 breast cancer patients after surgery. Among them, 130,746 patients received BCS, and the remaining 84,219 breast cancer patients underwent mastectomy. Although Asian or Pacific Islander (API) patients after surgery showed higher survival benefit than that of white patients in the primary data, after adjusting for age at diagnosis, luminal subtype, grade, T stage, and N stage in different races, white individuals had the longest period of survival was higher than that of the minority groups in BCS group(breast cancer-specific survival (BCSS): HRWhite versus API=0.402, HRWhite versus Black=0.132; p<0.001; overall survival (OS): HRWhite versus API=0.689, HRWhite versus Black=0.254; all p<0.001) and mastectomy group (BCSS: HRWhite versus API=0.325, HRWhite versus Black=0.128; p<0.001; OS: HRWhite versus API=0.481, HRWhite versus Black=0.206; all p<0.001) Conclusions: We first identified that the survival benefit of the minority group after surgery was lower than that of white individuals, regardless of tumor chrematistics and surgery types.